Analisis Kesalahan Sintaksis Pada Karangan Deskripsi Bahasa Jerman - Murad, Dhesy Bonitha Savitri; Azizah, Laelah; Mannahali, Misnah (Interference: Journal of Language, Literature, and Linguistics, 2021)
This study aims to determine the types of syntactic errors in the essay descriptions of the German language of SMA NEGERI 9 Makassar students. This type of research is descriptive qualitative. The analytical method used is the method proposed by Ellis. The research data is in the form of descriptive essays written by students. The data source of this research is the students of class XII Mia 8 SMA Negeri 9 Makassar, amounting to 31 students. The data collection technique was carried out through a German writing test. The results of the data analysis show that the syntactic errors that appear are phrase errors, including 4 types of errors in noun phrases, 8 types of errors in pronouns, 7 types of errors in prepositional phrases, 4 types of errors in adjective phrases, and 4 types of verb phrases.Â